2001
DOI: 10.2176/nmc.41.293
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Functional Distribution in the Corticospinal Tract at the Corona Radiata: A Three-dimensional Anisotropy Contrast Study.

Abstract: The spatial functional distribution of the nerve fibers was investigated in the corticospinal tract at the level of the corona radiata. Thirteen patients with corona radiata infarction underwent axial singleshot echo planar diffusion-weighted magnetic resonance imaging using a 1.5 Tesla scanner. Image analysis used the three-dimensional anisotropy contrast (3DAC) method to demarcate the nerve fibers in the corticospinal tract. Axial 3DAC images demonstrated the corticospinal tract as a distinct area indicating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…DW or DT imaging in the acute phase have the potential to predict motor function outcome in patients with ischemic or hemorrhagic diseases [13,14,15,21]. Decreased FA values in the remote pyramidal tract after stroke are associated with Wallerian degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…DW or DT imaging in the acute phase have the potential to predict motor function outcome in patients with ischemic or hemorrhagic diseases [13,14,15,21]. Decreased FA values in the remote pyramidal tract after stroke are associated with Wallerian degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have used various methods to locate the CST in the human brain [4,6,12,[16][17][18][19][20][21]24,28,34,35,[39][40][41]. In earlier studies, invasive methods such as dissection of the brain or direct electrical stimulation were used [6,12,16,17,28,35], however, the development of radiologic techniques such as brain CT and MRI enabled more recent studies to be conducted using noninvasive methods [18][19][20]39,40].…”
Section: The Evaluation Methods Used To Locate the Cstmentioning
confidence: 99%
“…There have been several studies conducted that have described the location of the CST in the CR [21,26,37,38,41]. In 1996, Tohgi et al measured the relative distance to the center of an infarct from the anterior pole to the posterior pole of the lateral ventricle in patients with CR infarct using brain CT.…”
Section: The Location Of the Cst At The Corona Radiatamentioning
confidence: 99%
“…Clinical recovery observations and brain MRI and DTT findings indicated that the stroke patients examined during the present study were able to walk without a functioning lateral CST of the affected hemisphere. These stroke patients initially showed complete hemiplegia due to a lesion in the corona radiata, the known pathway of CST (posterior portion of the corona radiata) [8][9][10]. The motor function of affected legs was slowly recovered over 3 months or more, to the extent of being able to overcome gravity.…”
Section: Discussionmentioning
confidence: 99%
“…We recruited 10 consecutive stroke patients from among stroke patients admitted for rehabilitation over an 18-month period, according to the following selection criteria: (1) a duration of more than 6 months since stroke onset; (2) an ability to walk on even ground without an assisting device; (3) complete paralysis of the affected upper and lower extremities at the time of stroke onset and a motor recovery time of at least 3 months enabling movement of the affected hip and knee extensor muscles against gravity; (4) brain MRI evidence of CST pathway injury at the corona radiata [8][9][10], as confirmed by a neuroradiologist; and (5) the CST confined within the brainstem or absent, even if the fractional anisotropy (FA) value was set as low as 0.1, owing to severe Wallerian degeneration.…”
Section: Methodsmentioning
confidence: 99%